1995
DOI: 10.1164/ajrccm.152.6.8520780
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal staging of non-small-cell lung cancer with positron emission tomography.

Abstract: To determine the usefulness of positron emission tomography with fluoro-2-deoxyglucose (PET-FDG) in assessing mediastinal disease in patients with non-small-cell lung cancer (NSCLC) and to compare its yield to that of computed tomography (CT), we performed a prospective consecutive sample investigation in a university hospital and its related clinics. In 30 patients with NSCLC with clinical stage I (T1-2, NO, MO) disease, we compared the results of chest CT and PET-FDG with the findings at surgical exploration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Several studies have evaluated the role of FDG PET for staging lung carcinoma. Most investigators have used focal techniques and concentrated on mediastinal lymph node staging [5][6][7][8][9]. Concerning the detection of distant metastases by whole-body FDG PET, three studies have already been published showing that the technique has excellent accuracy [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the role of FDG PET for staging lung carcinoma. Most investigators have used focal techniques and concentrated on mediastinal lymph node staging [5][6][7][8][9]. Concerning the detection of distant metastases by whole-body FDG PET, three studies have already been published showing that the technique has excellent accuracy [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…This uptake can be used in PET studies to visualize the tumour with high contrast compared with the surrounding tissue [2][3][4]. Considerable experience is now available on the diagnostic value of FDG PET in the mediastinal staging of lung cancer [5][6][7][8][9] but analysis of the efficiency of FDG PET for the detection of distant metastasis remains fragmentary [10][11][12]. This paper reports our current clinical experience in 110 patients with nonsmall cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…In the other patients, PET modified the therapeutic strategy by allowing us to adopt either a more curative approach or a more palliative approach than initially planned. Recent studies have shown that mediastinal 18 FDG uptake correlates well with the extent of mediastinal involvement in NSCLC [13,[16][17][18][19][20][21]. In particular, STEINERT et al [21] showed that 18 FDG-PET is superior to CT for nodal staging of NSCLC and help in surgical planning by enabling correct differentiation of N0 or N1 disease from N2 or N3 disease.…”
Section: Discussionmentioning
confidence: 99%
“…These studies must be separated into two groups, Some investigators have used focal techniques and have concentrated on hilar and mediastinal lymph node staging, while others have used whole-body techniques and have evaluated extrathoracic (Table 2) [49,[110][111][112][113][114][115][116][117][118][119]. The reported sensitivity for lymph node staging in non-small cell lung cancer varies from 82% to 100% and the specificity from 73% to 100%.…”
Section: Fig 2 Malignant Solitary Pulmonary Nodule (Adenosquamous Cmentioning
confidence: 99%